Pengaruh Model Problem Based Learning dalam Pembelajaran Teks Narasi Siswa Kelas VII MTs Muhammadiyah Kota Jambi - Shelviana, Zeni Fransisca; Yusra, Yusra; Wini, Lusia Oktri (Jurnal Ilmiah Dikdaya, 2024)
The aim of this research is to determine the influence of the problem based learning model in learning narrative texts for class VII students at MTs Muhammadiyah Jambi city. The approach in this research uses a quantitative approach with an experimental research approach with two groups of data. Data collection was carried out by means of interviews, observations, documentation in the field, and tests. The results of this research show that there is an effect after using the problem-based learning model compared to the conventional model, the results of the narrative essay writing skills test of students taught using the Problem-Based Learning model are higher than students taught using the conventional model. It can be concluded that the use of the problem based learning (PBL) method in learning narrative texts in classes VII A and VII B has quite an influence on the narrative text learning process.